The Mediating Role of E-Trust in the Relationship of E-Rating, E-Review, and Cash on Delivery System on Customer Purchasing Decisions: Evidence from Tiktok Shop Platform in Rantauprapat - Utami, Nur Izzati Presty; Siregar, Zulkifli Musannip Efendi; Rafika, Mulya (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to determine the effect of e-rating, e-review, and the cash-on-delivery (COD) system on e-trust and also on online purchasing decisions on the TikTok shop platform in Rantauprapat. The population in this study are consumers who own the TikTok application and use the TikTok shop platform in Rantauprapat, whose number is not known with certainty. The number of samples used in this study was 100 people with certain predetermined criteria. Sampling using non-probability sampling technique with the purposive sampling method. The data used in this research is primary data. The data analysis tool used is SEM analysis with Smart PLS software tools. The results obtained from this study indicate that e-rating has no significant effect on purchasing decisions, e-rating has no significant effect on e-trust, e-review has no significant effect on purchasing decisions, e-review has a positive and significant effect on e-trust, cod payment system has no significant effect on purchasing decisions, the COD payment system has a positive and significant effect on e-trust, and e-trust has a positive and significant effect on purchasing decisions.